2022
DOI: 10.1097/aog.0000000000005026
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hospital Surgical Volume With Survival in Early-Stage Cervical Cancer Treated With Radical Hysterectomy

Abstract: To evaluate the association of number of radical hysterectomies performed per year in each center with disease-free survival and overall survival. METHODS: We conducted an international, multicenter, retrospective study of patients previously included in the Surveillance in Cervical Cancer collaborative studies. Individuals with International Federation of Gynecology and Obstetrics (FIGO) 2009 stage IB1-IIA1 cervical cancer who underwent radical hysterectomy and had negative lymph nodes at final histology were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The number of radical hysterectomies is decreasing in developed country, even in high-volume centers [ 32 ]. However, the hospital surgical volume significantly affects the oncologic outcomes of cervical cancer after a radical hysterectomy [ 33 34 ]. As the volumes decrease and experience with the procedure declines, we must reconsider the significance of radical hysterectomy and parametrial resection, and further investigation is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The number of radical hysterectomies is decreasing in developed country, even in high-volume centers [ 32 ]. However, the hospital surgical volume significantly affects the oncologic outcomes of cervical cancer after a radical hysterectomy [ 33 34 ]. As the volumes decrease and experience with the procedure declines, we must reconsider the significance of radical hysterectomy and parametrial resection, and further investigation is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, referral to large-volume tertiary centers remains an important issue when dealing with patients with cervical cancer. 31 Moreover, this highlights the importance of adequate training on RH 32 to future generations of gynecologic oncology surgeons who will need to continue performing tailored radical surgery based on tumor characteristics.…”
Section: Commentmentioning
confidence: 99%
“…A systematic review of the literature including 2,662 women demonstrated no significant association between mortality and simple vs. radical hysterectomy in patients with microscopic disease, and the recent SCCAN retrospective trial of 1,257 patients comparing type B, C1 and C2 radical hysterectomy techniques found no survival difference for tumors up to 2 cm with increased radicality of surgery [ 11 12 ].…”
mentioning
confidence: 99%